Pengaruh Pemberian Kompres Bawang Merah Terhadap Penurunan Suhu Tubuh Pada Balita Demam - Rati Purwati; Rika Armalini; Puja Maya Sari; Tri Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2025)
Toddlers or children 1-4 years old are very susceptible to diseases and this disease often causes symptoms such as fever. Fever if not treated properly can cause higher temperatures and negatively impact children such as dehydration, lack of oxygen, neurological damage, and seizures. Fever in toddlers can be treated in several ways, one of which is through non-pharmacology such as onions. The goal is to find out whether or not there is an effect of shallot compresses on children with fever in Jorong Padang Candi. Research method: this study uses a pre-experiment approach with one group pretest-posttest Design. The sample in this study amounted to 10 toddlers. Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed that the average body temperature before the shallot compress treatment was 5 people (50%) and after the treatment experienced a change in body temperature of 37.4°C as many as 5 people (50%). Wilcoxon's results were found that the p value = 0.004 was smaller than the value (p < 0.05), meaning that there was an effect of shallot compresses with a decrease in body temperature in fever children. It was concluded that onion compresses can significantly lower body temperature in toddlers who have a fever. It is hoped that parents will be able to provide shallot compress intervention to lower the body temperature of toddlers well before being given further treatment.